An Analysis of Child Abuse Detected by Skeletal Surveys Before and During the COVID‐19 Pandemic - Vincent R. Li; Trevor A. Pickering; Karen Kay Imagawa; Joseph M. Rich; Amit S. Sura (Pediatric Discovery)
ABSTRACT The COVID‐19 pandemic and the stay‐at‐home order may have impacted the risk of child physical abuse (CPA). Analyzing injury types in suspected CPA cases before and during the pandemic can provide valuable insights. The objective of this study is to compare the incidences and types of injuries detected by skeletal surveys in suspected CPA cases at a large academic children's hospital before and during the COVID‐19 pandemic. The study compared the incidences and proportion of specific injury sites, types of traumas, and demographic characteristics before and during the pandemic using Pearson's chi‐squared and Fisher's exact tests. A total of 479 patients who underwent skeletal surveys were included, with 306 patients sampled before the pandemic (63.8%) and 173 patients sampled during the pandemic (36.1%). There were no significant differences in age, gender, or ethnicity between the two groups. Highly suspicious CPA incidences were similar before (0.87/month) and during (0.81/month) the pandemic, reflecting 10.5% and 11.6% of all patients who underwent skeletal surveys, respectively. There were no significant demographic differences between the groups. However, the proportion of patients with intracranial or retinal hemorrhage significantly decreased (p < 0.05) during the pandemic, with no significant differences in types of skeletal fractures. In conclusion, the overall incidence of CPA remained similar before and during the pandemic. The significant decrease in intracranial and retinal hemorrhages suggests a potential change in injury patterns or reporting. Further research is needed to understand the factors contributing to these findings. Clinical Trial Registration This study is a retrospective clinical trial and therefore not subject to clinical trial registration requirements.